KARAKTERISTIK PEWARNA ALAMI DARI EKSTRAK KULIT BUAH JERUK MANDARIN (Citrus reticulata) PADA PERBANDINGAN PELARUT ETANOL DAN KLOROFORM - Saraswati, Sagung Ayu Bulan Julia; Wrasiati, Luh Putu; Wartini, Ni Made (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2018)
Orange fruit who be the superior commodity is known as a fruit who rich of its vitamin C. One kind of orange who really liked by the society is Mandarin Orange (Citrus reticulata) that comes from China. The aims of this research were to know the effect of ethanol and chloroform solvent ratio to the characteristic of the natural colorant from Mandarin orange peel extract and determine the best ethanol and chloroform solvent ratio which produced Mandarin orange peel extract as natural colorant. Experimental design in this research used Randomized Block Design by using the comparison of ethanol and chloroform solvents that consist of 6 levels, there are: ethanol : chloroform (0:10); ethanol : chloroform (2:8); ethanol : chloroform (4:6); ethanol : chloroform (6:4); ethanol : chloroform (8:2); ethanol : chloroform (10:0). The treatment was repeated as many as 3 repetitions then obtained 18 units of the experiment. The data were analyzed by variance and if the treatment had a effect on the variable then continued with Duncan test. The result showed that ethanol and chloroform solvent ratio had significant effect on the yield, the total carotenoids content, the level of brightness (L*), the level of redness (a*), the level of yellowness (b*) of Mandarin orange peel extract. Based on the results of index effectiveness test used five expert, the ethanol and chloroform solvent ratio of 0 :10 produced the best characteristic of Mandarin orange peel extract with the yield 4.83 ± 0.22f (%), the total carotenoids content 3.56 ± 0.20a (%), the level of brightness (L*) 31.34 ± 0.63d, the level of redness (a*) 28.39 ± 0.69a, and the level of yellowness (b*) 34.52 ± 0.18a. Keywords : Citrus reticulata, extraction, ethanol, chloroform, natural colorant